Characteristics and origin of lacustrine source rocks in the Lower Cretaceous, Erlian Basin, northern China. (September 2015) - Ding, Xiujian; Liu, Guangdi; Zha, Ming; Huang, Zhilong; Gao, Changhai; Wang, Pangen; Qu, Jiangxiu; Lu, Xuejun; Chen, Zhelong
Abstract: Four lacustrine rift sub-basins in the Erlian Basin, one of the most petroliferous basins in northern China, have been analyzed to characterize source rock potential, to reveal environmental and ecological changes and to construct depositional models for lacustrine source rocks in different tectonic settings. The first member of the Tengger Formation in these sub-basins is characterized by a wide range of total organic carbon contents, hydrogen indices and kerogen types. These sub-basins have dissimilar boundary fault activities and sedimentation rates. The differences in border fault activity and sedimentation rate are consistent with changes in productivity, redox conditions and clastic influx input. The carbon isotopic composition of carbonates in mudstone samples suggests that the productivity of Aer and Wuli sub-basins is higher than that of Naoer and Saihan sub-basins. Differences in tectonic conditions also result in different redox conditions of depositional environments. Total reduced sulfur and Pr/Ph ratios show an oxidizing environment in Aer and Wuli sub-basins; while a reducing environment was present in Naoer and Saihan sub-basins. With more active boundary faults and higher sedimentation rates, the terrigenous organic matter inputs to Aer and Wuli sub-basins are higher than Naoer and Saihan sub-basins. This can be confirmed by relative steranes abundances. Different tectonic conditions existed in different sub-basins, which lead to variations in ecological communities in the lake systems. These environmental and ecological changes enable us to construct models for the deposition of lacustrine source rocks under different tectonic backgrounds. During source rock deposition in Aer and Wuli sub-basins, the high influx of clastic sediments carrying high terrigenous organic matter and dissolved inorganic carbon and nitrate into the lake, might have sustained high productivity and oxidizing conditions. Due to high influx of clastic sediments and unstable water column stratification, the depositional environment of Aer and Wuli sub-basins are oxidizing. In a high productivity lake, there is still significant organic matter accumulation in oxidized environment after oxidative degradation. The high productivity is the dominant factor controlling the formation of organic rich sediments and the deposition of source rocks in Aer and Wuli sub-basins. In Naoer and Saihan sub-basins, the depositional environment during source rock formation is reducing due to low influx of clastic sediments with low productivity. In low productivity lakes, such as Naoer and Saihan sub-basins, which are low productivity lakes, redox condition substitutes for productivity and becomes the predominant factor controlling the formation of lacustrine source rocks. It is evident that the synergetic evolution of depositional environments and organisms in a lake system accounts for the formation of source rocks with different characteristics. The proposed models may have important implications for source rock prediction in other lacustrine rift basins. Highlights: Source rocks from the Erlian Basin were analyzed with geochemical techniques. We confirm major factors that control the lacustrine source rocks development. We construct models for origin of lacustrine source rocks under different tectonics.